Preserved leftward movement in left unilateral spatial neglect due to frontal lesions. - Ishiai, S (1994)
Three patients with left unilateral spatial neglect after predominantly frontal lobe lesions were asked to extend a horizontal line leftwards to double its original length. In this line extension task, they readily executed movements in or towards the contralesional left space. They performed the task in the left and right hemispaces as well as in the midline. The mean extension lengths did not differ significantly among these three spatial conditions. These results suggest that directional hypokinesia takes little part in left unilateral spatial neglect due to frontal lobe lesions. It is considered that the patients could execute leftward movements as the task oriented their attention sufficiently to the left. Two of the three patients, like reported cases with frontal neglect, showed a typical exploratory deficit for the left space in the line cancellation test. Such a deficit found in the traditional tasks, however, does not mean the presence of directional hypokinesia. All three patients showed visual extinction on double simultaneous stimulation. An attentional mechanism seems to play a predominant part in unilateral spatial neglect due to frontal lesions.